ANALYSIS OF FACTOR FACTORS AFFECTING FIRM VALUE WITH DIVIDEND POLICY AS MODERATING VARIABLES IN REGISTERED BANKING COMPANIES IN INDONESIA STOCK EXCHANGE - Hutapea, Nicky Astria (Asosiasi Dosen Akuntansi Indonesia, 2019)
The purpose of this study was to determine and analyse the effect of liquidity, capital adequacy ratio (CAR), growth, size, profitability on firm value and dividend policy as a moderating variable on banking companies listed on the Indonesia Stock Exchange. The population of this research is 43 companies listed on the Indonesia Stock Exchange with an observation year 2013 to 2017. The sample is 145 and selected using the purposive sampling method. Data is processed using panel data regression statistical test methods. The results of this study prove that liquidity and capital adequacy ratios do not affect firm value while growth, size, profitability positively affect firm value in banking companies listed on the Indonesia Stock Exchange. Dividend policy is able to moderate the effect of liquidity, capital adequacy ratio, growth, size, profitability on firm value in banking companies listed on the Indonesia Stock Exchange.